Implementation of a responsible conduct of research education program at Duke University School of Medicine. (4th July 2019) - Simon, Christian; Beerman, Rebecca W.; Ariansen, Jennifer L.; Kessler, Donna; Sanchez, Ana M.; King, Kindra; Sarzotti-Kelsoe, Marcella; Samsa, Gregory; Bradley, Ann; Torres, Laurianne; Califf, Robert; Swamy, Geeta K.
ABSTRACT: Academic medical centers rarely require all of their research faculty and staff to participate in educational programs on the responsible conduct of research (RCR). There is also little published evidence of RCR programs addressing high-profile, internal cases of misconduct as a way of promoting deliberation and learning. In the wake of major research misconduct, Duke University School of Medicine (DUSoM) expanded its RCR education activities to include all DUSoM faculty and staff engaged in research. The program included formal deliberation of the Translational Omics misconduct case, which occurred at Duke. Over 5, 000 DUSoM faculty and staff participated in the first phase of this new program, with a 100% completion rate. The article reports on the program's development, challenges and successes, and future directions. This experience at Duke University illustrates that, although challenging and resource intensive, engagement with RCR activities can be integrated into programs for all research faculty and staff. Formal, participatory deliberation of recent cases of internal misconduct can add a novel dimension of reflection and openness to RCR educational activities.